2020
DOI: 10.15537/smj.2020.8.25220
|View full text |Cite
|
Sign up to set email alerts
|

Epilepsy trigger factors in Saudi Arabia

Abstract: Objectives: To identify epilepsy triggers prevalent in Saudi Arabia with a view to seizure prevention or achieving a reduction in their frequency. Methods: This is part of a cross-sectional study carried out in 2020 in a Saudi population in the Kingdom of Saudi Arabia (KSA). We used an online questionnaire to evaluate the most common seizure trigger factors. Results: A total of 546 Saudi patients with epilepsy participated in the study, of which 289 (53%) were women. Of them, 263 (48.1%) had no seizure in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 17 publications
(19 reference statements)
0
2
0
Order By: Relevance
“…We found that the prevalence of breakthrough seizures is slightly higher in males than females, with a mean age of 6.8 ± 1.6 years, which may be due to more adherence and better compliance to medication in adults and underdeveloped immune systems in children [14,31].…”
Section: Discussionmentioning
confidence: 76%
“…We found that the prevalence of breakthrough seizures is slightly higher in males than females, with a mean age of 6.8 ± 1.6 years, which may be due to more adherence and better compliance to medication in adults and underdeveloped immune systems in children [14,31].…”
Section: Discussionmentioning
confidence: 76%
“…On the other hand, missing medication, emotional stress, and sleep deprivation are the most common triggering factor in adults, which is attributed to more susceptibility to infections in children than adults and underdeveloped immune systems in children. 2 , 21 …”
Section: Discussionmentioning
confidence: 99%
“…As for the patient's age, it ranged from 0 to 90 years and 8 studies showed a male predominance [ 11 , 17 , 21 , 22 , 25 , 26 , 28 , 31 ]. According to the family history of epilepsy, it was seen only in five studies [ 17 , 22 , 24 , 25 , 30 ] and showed a prevalence ranging from 6% to 24.9% [ 22 , 30 ].…”
Section: Reviewmentioning
confidence: 99%
“…Only six studies assessed the educational level of the participants; of these, four showed a predominance of high-school educational level [ 24 , 26 , 29 , 31 ]. While the predominance was for bachelor’s degrees of education in two studies [ 27 , 30 ].…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation